From traditional medicine to modern medicine: the importance of TCM regulatory science (TCMRS) as an emerging discipline - Hua Hua; Jian-Yuan Tang; Jun-Ning Zhao; Ting Wang; Jun-Hua Zhang; Jiang-Yong Yu; Chang-Ming Yang; Yan-Ling Ai; Qiao-Xian Luo (Chinese Medicine)
Abstract Traditional Chinese medicine (TCM) has become a standardized medical system through systematic development across global healthcare practices. However, concerns persist regarding the safety, efficacy and quality of traditional medicinal products. Traditional Chinese medicine regulatory science (TCMRS) has emerged as an interdisciplinary field to address these challenges. This discipline integrates multidisciplinary knowledge to develop new tools, standards and approaches for systematic evaluation of benefit-risk profiles. This approach aims to ensure the quality, safety, and efficacy of TCM products, while also supporting the development of scientifically grounded regulatory frameworks that accommodate traditional medicine’s distinctive characteristics. Through comprehensive quality management from raw material sourcing to production processes and clinical validation, developing and adopting TCMRS is entrusted to significantly strengthen its regulatory oversight. This review examines the critical scientific challenges in the modernization process of TCM, analyzes the conceptual foundations of TCMRS, evaluates its pivotal role in pharmaceutical transformation, and highlights its essential function in preserving traditional knowledge while fostering therapeutic innovation. Key challenges for TCMRS implementation include reconciling traditional epistemologies with modern pharmaceutical paradigms, standardizing complex herbal formulations, and developing rigorous evaluation protocols for decoctions and compound preparations. The integration of advanced methodologies, including systems biology, network pharmacology, artificial intelligence, and nanotechnology, into regulatory frameworks, combined with enhanced international cooperation, remains a crucial strategy for tackling global public health challenges. Future development trajectories for TCMRS will prioritize lifecycle management strategies, technology-driven innovation systems, and global knowledge-sharing initiatives, propelled by advancements in life sciences and information technology. This evolution requires careful balancing of three fundamental elements: theoretical development in traditional medicine, integration of emerging technologies, and maintenance of regulatory system stability. It is crucial to innovate the working mechanisms of the TCMRS researcher alliance and the global policy-coordination mechanism for TCM regulation, enhance the conversion of basic disciplines into regulatory applications, and support the establishment of an excellent TCM regulatory system with scientific decision-making. These efforts are essential for promoting the high-quality development of the TCM industry and boosting its international influence and presence.